In Vitro Anti-Inflammatory Assay of Bitter Melon (Momordica charantia L.) Ethanol Extract - Rahmawati Rahmawati; Harti Widiastuti; Eka Sulistya (Jurnal Fitofarmaka Indonesia, 2020)
Bitter melon contains flavonoids that have anti-inflammatory function. Inflammation can be caused by protein denaturation. This research tested the anti-inflammatory potential of ethanol extract of leaves and bitter melon (Momordica charantia L.) using a UV-Vis spectrophotometer and protein denaturation inhibition method. There were three experimental groups formed in this research including negative control group, positive control group, and test solutions. Diclofenac sodium was used in the positive control group at concentration series of 1, 2, 4, 8, and 16 ppm, obtaining a regression equation Y = 3.546X + 2.163 and r = 0.9990. Whilst, for bitter melon ethanol extract at a series of concentrations of 10, 20, 40, 80 and 160 ppm obtained a regression equation Y = 0.243X + 11.74 and r = 0.9995. The potential of diclofenac sodium as an anti-inflammatory agent was shown by IC50 of 13.490 µg / mL, while the ethanol extract of bitter melon fruit has an IC50 of 157.448 µg / mL. This result indicated that bitter melon ethanol extract had the potential as moderate anti-inflammatory agent.